Effects of technological innovation capabilities on organizational agility : a research focused on the r&d centers in Turkey - Hatunoğlu, Şükrü Barış (My University, 2023)
Bu araştırma, teknolojik yenilik yeteneklerinin örgütsel çeviklik üzerindeki etkilerini keşfetmektedir. Çalışma, örgüte ait fonksiyonel ve dinamik inovatif yeteneklerin firmaların proaktif, yanıt verebilir, radikal ve adapte olabilir becerilerini ne ölçüde arttırdığını değerlendirmeyi amaçlamıştır. Yenilikçi yetenekleri ayrıntılı bir şekilde ölçebilmek için türkiyedeki ar ge merkezleri örneklem olarak seçilmiştir. Toplamda 320 adet yönetici seviyesindeki çalışandan toplanan verilerin ışığında, organize etme, imalat ve pazarlama yeteneklerinin örgütsel çeviklik üzerinde belirgin ve pozitif yönlü etkilere sahip olduğu bulunmuştur.

This research explores the effects of technological innovation capabilities on organizational agility. The study aimed to evaluate the extent to which the functional and dynamic innovative capabilities of the organization increase the proactive, responsive, radical and adaptive capabilities of the firms. In order to measure innovative capabilities in detail, R&D centers in Turkey were chosen as a sample. In the light of the data collected from a total of 320 executive-level employees, it has been found that organizing, manufacturing and marketing skills have significant and positive effects on organizational agility.
Keywords: Araştırma kurumları; Business; İşletme; Organizational agility; Örgütsel çeviklik; Research institutes; Technological innovation capabilities; Technological innovations; Teknolojik yenilik yetenekleri; Teknolojik yenilikler; Turkey; Türkiye